Role of Melatonin as an Adjunctive Treatment for Depression and Cognitive Impairment in Hemodialysis Patients: A Randomized, Double-Blind Clinical Trial - Shima Hatamkhani; Sepideh Roshan; Afshin Shiva (Iranian Journal of Psychiatry)
Objective: Chronic kidney disease (CKD) is a pervasive health issue associated with various complications, including cognitive impairment and depression among patients undergoing hemodialysis. This study aimed to assess the impact of melatonin on depression and cognitive function in hemodialysis patients. Method: A randomized, double-blinded, placebo-controlled clinical trial was conducted in 50 hemodialysis patients, with half of the patients receiving 3 mg daily melatonin and the other half receiving a placebo for two months. Depression and cognitive function were evaluated using the Beck Depression Inventory (BDI) and Mini-Mental State Examination (MMSE) questionnaire, respectively. Quantitative variables were analyzed using a t-test. The Chi-square test also evaluated qualitative variables. Quantitative data were analyzed by covariance analysis before and after the intervention. Results: Hypertension was the most prevalent underlying condition among study participants, affecting 40% of the intervention group. The intervention group exhibited baseline depressive symptoms (mean BDI score: 16.12 ± 7.12), which significantly improved post-intervention (13.6 ± 6.6). Notably, both the intervention and control groups demonstrated significant reductions in depressive symptoms, as assessed by paired t-tests (P = 0.033 and P = 0.02, respectively). Cognitive function, as measured by the MMSE, improved in both groups (1.28 ± 0.81 for melatonin, 1.52 ± 0.1 for placebo), with significant within-group differences (P = 0.048 and P = 0.002, respectively). ANCOVA analysis revealed no significant between-group differences in BDI scores (F(1,47) = 0.196, P = 0.66, partial eta-squared = 0.004). and in MMSE scores (F(1,47) = 0.003, P = 0.954, partial eta-squared = 0.00) post-intervention. Conclusion: While this study did not demonstrate significant effects of melatonin on depression and cognitive impairment in hemodialysis patients, positive changes were observed, warranting further research to optimize treatment regimens and explore the potential therapeutic benefits of melatonin in this patient population.